2020
DOI: 10.3390/jcm9041060
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Impact of Parental BMI on the Incidence of Overweight and Obesity in Children from Ukraine

Abstract: The aim of this study was to assess the impact of parental body mass index (BMI) on the risk of having an overweight or obese child in Ukraine. This study included 22,576 parents (11,288 mothers and fathers) and the same number of children (boys 48%, girls 52%) aged 6.0–18.9 years who live in Ukraine. The study was conducted in randomly selected primary, secondary and high schools of Ukraine. Body weight and height was measured in triplicate. Based on the results obtained, BMI was calculated. The analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
3
2
0
Order By: Relevance
“…In this study, the relationship between the incidence of paternal overweight and obesity was associated with the occurrence of overweight and obesity in children. This is in accordance with a study in Ukraine where children of overweight and obese fathers have a 1.4 to 2 time's higher risk of suffering from overweight and obesity [16]. This is thought to be due to the influence of genes and environmental and behavioral influences.…”
Section: Resultssupporting
confidence: 92%
“…In this study, the relationship between the incidence of paternal overweight and obesity was associated with the occurrence of overweight and obesity in children. This is in accordance with a study in Ukraine where children of overweight and obese fathers have a 1.4 to 2 time's higher risk of suffering from overweight and obesity [16]. This is thought to be due to the influence of genes and environmental and behavioral influences.…”
Section: Resultssupporting
confidence: 92%
“…Additionally, based on our results, higher parental BMI increases the likelihood of offspring being in the overweight/obesity group. In line with our findings, other studies confirm that excessive weight of parents is a risk factor for children's overweight/obesity (Dereń et al., 2020; Kumar et al., 2010). Evidence shows that parents with obesity tend to consume high‐calorie products and be less physically active; such behaviours can create an obesogenic environment.…”
Section: Discussionsupporting
confidence: 93%
“…Parental OW/OB was strongly associated with childhood OW/OB. Consistent with the present findings, studies from Ukraine and Iran found that children had higher BMI when their parents also had OW/OB [ 33 , 34 ]. The results of the WC-based analyses did not differ substantially from the BMI-based analyses [ 7 ].…”
Section: Discussionsupporting
confidence: 92%